Review, design, stabilization and synchronization of fractional-order energy resources demand-supply hyperchaotic systems using Fractional-order PD-based Feedback Control scheme - Ammar Soukkou; Yassine Soukkou; Sofiane Haddad; Mohamed Benghanem; Abdelhamid Rabhi (Archives of Control Sciences, 2023)
This paper introduces a fractional-order PD approach (F-oPD) designed to control a large class of dynamical systems known as fractional-order chaotic systems (F-oCSs). The design process involves formulating an optimization problem to determine the parameters of the developed controller while satisfying the desired performance criteria. The stability of the control loop is initially assessed using the Lyapunov’s direct method and the latest stability assumptions for fractional-order systems. Additionally, an optimization algorithm inspired by the flight skills and foraging behavior of hummingbirds, known as the Artificial Hummingbird Algorithm (AHA), is employed as a tool for optimization. To evaluate the effectiveness of the proposed design approach, the fractional-order energy resources demand-supply (Fo-ERDS) hyperchaotic system is utilized as an illustrative example.